PERAN TEKNOLOGI INFORMASI BAGI HUBUNGAN INTERORGANISASIONAL DALAM SUPPLY CHAIN MANAGEMENT SYSTEM - Endang Hariningsih (Jurnal Bisnis, Manajemen, dan Akuntansi, 2012)
The use of information technology (IT) is considered a prerequisite for the effective control of today’s complex supply chains. The use of information technology (IT) is thought to have wide ranging consequences for the organization of economic activities within firms and across firm boundaries.  The adoption of IT within firms has been closely associated with organizational changes such as process restructuring and the elimination of layers of management. Furthermore, companies have applied IT to improve their internal processes; they also have developed inter- organizational systems (IOS) linking suppliers, customers, and business partners to improve efficiency throughout the value chain. Objective of the paper is to discuss about the role of information technology in supply chain management system.Keyword: information technology, supply chain management system, inter-organizational system